Impacto da estratégia multimodal na adesão a higiene de mãos entre a equipe multiprofissional - Adriana Oliveira de Paula (2015)
Hand hygiene (HH) is the most important measure of prevention and control of healthcare associated infections (HAIs) due to its convenience, low cost and greater benefit. However, it is observed that the compliance to HH by healthcare workers is bellow the desired worldwide. Some strategies have been implemented in order to increase rates of adherence to HH. The World Health Organization (WHO) recommends the use of a multimodal strategy. In order to this, this study aimed to evaluate the impact of multimodal strategy in adherence to hand hygiene among the multidisciplinary team. It was a before and after study, held in two intensive care units of a university, tertiary care, public and large hospital. All professionals who provided direct care to patients between August 2013 and May 2015 were part of the population. Interventions followed the five key components proposed by the multimodal strategy of World Health Organization, named: changes in the system, training/education, evaluation/feedback, reminders in the organizational environment and safety climate. Two different data collection techniques were used: self-resported questionnaire (with questions regarding the knowledge of professionals about hand hygiene and the self-reported rates of HCW of HH), direct observation (opportunities of HH). Data were processed using SPSS. Descriptive, univariate analyzes (McNemar test, chi-square test or Fisher's exact test and t test or Mann Whitney test) and multivariate analyzes (logistic regression) were performed. It was considered a confidence interval of 95% with a significance level of 5%. The project was approved by the Ethics Committee of UFMG (COEP) (CAAE: 18477913.1.0000.5149). Study participants were 127 professionals, totalling 9,500 opportunities of HH (divided into three different observation moments). The HCW rates of adherence to HH by direct observation was 20.8% and the self-reported rate was 88.3% at baseline. However, the perception of adhesion of other professionals groups pointed rates from 51.3 to 79.1%. Professionals showed preference for handwashing in order to handrubbing, during self reported and observations. After the intervention, feedback and reminders in the organizational environment, HH rates among health care workers were 16.2% in the post-intervention period 1 and 15.7% in the post-intervention 2. However, they had a positive impact on improving the use of handrubbing with alcohol solution (post-intervention 1). Most professionals (88.0%) reported having the feeling of clean hands after performing handrub and considered the product used as pleasant, without reporting any intolerance. Regarding the self-assessment for the promotion and practice of hand hygiene, the institution was classified as basic, which is consistent with low rates of adherence found in this work. In this sense, the findings of this work, increase the challenge of improving HH, indicating a strong need for improvement and incentives for HH among health car workers.